2014
DOI: 10.1002/path.4415
|View full text |Cite
|
Sign up to set email alerts
|

Discoidin domain receptor 2 (DDR2) promotes breast cancer cell metastasis and the mechanism implicates epithelial–mesenchymal transition programme under hypoxia

Abstract: A wide range of genes involved in breast cancer metastasis have been reported to be related to the microenvironment. We studied the role of discoidin domain receptor 2 (DDR2), a collagen-binding receptor, in breast cancer progression under hypoxic conditions. We showed that DDR2 protein expression closely correlated with the expression of hypoxic marker HIF-1α in clinical breast cancer specimens. The in vitro data demonstrated that hypoxia treatment increased the levels of both expression and phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 45 publications
6
56
3
Order By: Relevance
“…It was found that under DDR2 silencing condition, the rates of migration and invasion of the cells were significantly inhibited when compared with the control cells. Similar to our results, recent reports have indicated that DDR2 is crucial for the migration and invasion of breast and prostate cancer cells [17,18]. In addition, DDR2 silencing reduced experimental liver metastasis of human A375 cells [2].…”
Section: Discussionsupporting
confidence: 81%
“…It was found that under DDR2 silencing condition, the rates of migration and invasion of the cells were significantly inhibited when compared with the control cells. Similar to our results, recent reports have indicated that DDR2 is crucial for the migration and invasion of breast and prostate cancer cells [17,18]. In addition, DDR2 silencing reduced experimental liver metastasis of human A375 cells [2].…”
Section: Discussionsupporting
confidence: 81%
“…4). A signalling connection between collagen and ERK activation was previously identified, although mainly associated with cancer cell migration and invasion4748. Thus our data now provide an additional layer of the interplay between collagen, ERK signalling and cell survival.…”
Section: Discussionsupporting
confidence: 73%
“…HT1080 cells express both DDR1 and DDR2 (Fig. 2 B ), and MDA-MB231 cells are also known to express both DDRs (20, 2628). As shown in Fig.…”
Section: Resultsmentioning
confidence: 98%